168k views
3 votes
(3t^5)^-3

A 9/t^15
B 3/t^15
C 27/t^15
D 1/27t^15


(x/2y^5)^-2
A x^2/4y^10
B 4y^25/x^2
C 4y^10/x^2
D x^2/4y^25

User Lindauson
by
5.5k points

1 Answer

4 votes

Answer:
\bold{D)\quad (1)/(27t^(15))}
\bold{C)\quad (4y^(10))/(x^2)}

Explanation:

The negative flips the numerator to the denominator and vice versa.


(3t^5)^(-3)\quad =(1)/((3t^5)^(3))\quad =(1)/(3^3\cdot t^(5\cdot 3))\quad =\large\boxed{(1)/(27t^(15))}


\bigg((x)/(2y^5)\bigg)^(-2)\quad =\bigg((2y^5)/(x)\bigg)^2\quad =(2^2\cdot y^(5\cdot 2))/(x^2)\quad =\large\boxed{(4y^(10))/(x^2)}